Effects of galactooligosaccharides on maternal gut microbiota, glucose metabolism, lipid metabolism and inflammation in pregnancy: A randomized controlled pilot study - Wan, Jiayang; An, Lin; Ren, Zhenghong; Wang, Shuxian; Yang, Huixia; Ma, Jingmei (Frontiers in Endocrinology, 2023)
Background: Gut microbiota of pregnant women change with the gestational week. On the one hand, they participate in the metabolic adaptation of pregnant women. On the other hand, the abnormal composition of gut microbiota of pregnant women is more likely to suffer from gestational diabetes mellitus (GDM). Therefore, gut microbiota targeted treatment through dietary supplements is particularly important for prevention or treatment. Prebiotic supplements containing galactooligosaccharides (GOS) may be an intervention method, but the effect is still unclear. Objective: This study aims to evaluate the feasibility and acceptability of prebiotic intervention in healthy pregnant women during pregnancy, and to explore the possible effects of intervention on pregnant women and the influence on gut microbiota as preliminaries. Methods: After recruitment in first trimester, 52 pregnant women were randomly assigned to receive GOS intervention or placebo containing fructooligosaccharides. 16S rRNA sequencing technology was used to detect the composition, diversity and differential flora of gut microbiota. Lipid metabolism, glucose metabolism and inflammatory factors during pregnancy were also analyzed. Results: The adverse symptoms of GOS intervention are mild and relatively safe. For pregnant women, there was no significant difference in the GDM incidence rates and gestational weight gain (GWG) in the GOS group compared with placebo (P > 0.05). Compared with the placebo group, the levels of FPG, TG, TC, HDL-C, and LDL-C had no significant difference in GOS group (P > 0.05). However, compared with placebo group, chronic low-grade inflammation index IL-6 showed a downward trend in GOS group (P = 0.080). For newborns, there was no significant difference between GOS group and placebo group in the following variables including gestational week, birth weight, and birth length (P > 0.05). And compared with the placebo group, the GOS group had a higher abundance of Paraprevotella and Dorea, but lower abundance of LachnospiraceaeUCG_001. Conclusions: GOS prebiotics appear to be safe and acceptable for the enrolled pregnancies. Although GOS intervention did not show the robust benefits on glucose and lipid metabolism. GOS can be considered as a dietary supplement during pregnancy, and further clinical studies are needed to explore this in the future.